A New Method for Characterizing Very Low-Mass Companions with Low-Resolution Near-Infrared Spectroscopy. (4th January 2016) - Rice, Emily L.; Oppenheimer, Rebecca; Zimmerman, Neil; Roberts, Lewis C.; Hinkley, Sasha
Abstract: We present a new and computationally efficient method for characterizing very low-mass companions using low-resolution ( R ∼ 30), near-infrared ( YJH ) spectra from high-contrast imaging campaigns with integral field spectrograph (IFS) units. We conduct a detailed quantitative comparison of the efficacy of this method through tests on simulated data comparable in spectral coverage and resolution to the currently operating direct-imaging systems around the world. In particular, we simulate Project 1640 data as an example of the use, accuracy, and precision of this technique. We present results from comparing simulated spectra of M, L, and T dwarfs with a large and finely sampled grid of synthetic spectra using Markov-chain Monte Carlo techniques. We determine the precision and accuracy of effective temperature and surface gravity inferred from fits toPHOENIX dusty and cond, which we find reproduce the low-resolution spectra of all objects within the adopted flux uncertainties. Uncertainties in effective temperature decrease from ± 100-500 K for M dwarfs to as small as ± 30 K for some L and T spectral types. Surface gravity is constrained to within 0.2-0.4 dex for mid-L through T dwarfs, but uncertainties are as large as 1.0 dex or more for M dwarfs. Results for effective temperature from low-resolution YJH spectra generally match predictions from published spectral type-temperature relationships except for L-T transition objects and young objects. Single-band spectra (i.e., narrower wavelength coverage) result in larger uncertainties and often discrepant results, suggesting that high-contrast IFS observing campaigns can compensate for low spectral resolution by expanding the wavelength coverage for reliable characterization of detected companions. We find that S/N ∼ 10 is sufficient to characterize temperature and gravity as well as possible given the model grid. Most relevant for direct-imaging campaigns targeting young primary stars is our finding that low-resolution near-infrared spectra of known young objects, compared to field objects of the same spectral type, result in similar best-fit surface gravities but lower effective temperatures, highlighting the need for better observational and theoretical understanding of the entangled effects of temperature, gravity, and dust on near-infrared spectra in cool low-gravity atmospheres.